Biocentric and Life Course Perspectives on Risk Perception of COVID-19 and Climate Change: A Narrative Review - Akhlaghi Pirposhteh, Elham; Mishmast, Mohammadreza; Babaei Pouya, Amin; Khammar, Alireza; Salehi Sahlabadi, Ali; Eshaghzadeh, Maliheh; Porsadeghiyan, Mohsen (Shahroud Journal of Medical Sciences, 2026)
Background: Climate change (CC) and the COVID-19 pandemic are global crises that demand urgent policy attention. Although different in cause and timeline, both threaten health, livelihoods, and social stability. This study examines risk perception for COVID-19 and CC using a biocentric, Life Course perspective. We treat them as two sides of the same coin. Methods: We performed a narrative review. Databases searched: Scopus, Web of Science, PubMed, and Google Scholar. Keywords included: COVID-19, climate change, global warming, risk perception, understanding, life center, and biocentric. Relevant studies were screened and synthesized to extract key findings. Results: Both hazards have global health impacts and need coordinated biocentric responses. COVID-19 is acute and fast CC is chronic and slow. Both show poor public understanding of long-term risk. Risk awareness varies by population and life stage. Policies often ignore ecological and intergenerational effects. Conclusions: Risk perception for CC and COVID-19 remains uneven and underdeveloped. A Life Course approach centering biology, ecology and development across lifespans can improve responses. We recommend greater public engagement and participatory solutions. Policymakers should shift from human-centered to Life Course frameworks to support ecological health and intergenerational resilience.